Analisis Implementasi Fungsi Manajemen pada Event Jatim Open 2026 - Azizatul Fitriani; Catur Supriyanto (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2026)
This study aims to measure and describe the level of implementation of management functions in the 2026 East Java Open event based on the perceptions of the committee, athletes, and relevant stakeholders. This study used quantitative descriptive research with descriptive statistical analysis techniques. The research findings indicate that planning obtained an average score of 27.06, organizing obtained an average score of 26.56, implementation obtained an average score of 26.26, and controlling obtained an average score of 26.08. Therefore, it can be concluded that planning is an implementation that must be considered by the 2026 Jatim Open event to maximize event planning. Organizing, actuating, and controlling also need to be considered to support the planning process. Every strategy requires proper planning and implementation. Therefore, the 2026 Jatim Open event must consider the implementation of planning, organizing, actuating, and controlling in its event implementation. Keywords: Actuating, Controlling, Organizing, Planning